PSYCHOLOGICAL HEALTH OF UNIVERSITY STUDENT’S PRACTITIONERS OF SPORT AND ITS RELATIONSHIP WITH CERTAIN VARIABLES - Al-Nader, Haitham Mohammad; Al-Rhamnh, Aziz Ahmed; Algafari, Maysoon Abdelwahab A. (European Scientific Journal, ESJ, 2013)
The present study aims to determine the levels of students’ psychological health, systematically comparing regular practitioners of exercise to students who do not practice any organized athletic activity in Jordanian universities. It will also seek to determine the relationship between psychological health variables, sex, and college GPA. The study sample consisted of (200) students, of whom (113) were males and (87) were females, from various grade levels and different disciplines. Results indicated that there were differences in psychological health between students who practiced sports and students who did not practice any sports, while there were no differences in psychological health due to gender, college, or GPA.